MAP Training My Brain™: Meditation Plus Aerobic Exercise Lessens Trauma of Sexual Violence More Than Either Activity Alone - Shors, Tracey J.; Chang, Han Y. M.; Millon, Emma M. (Frontiers in Neuroscience, 2018)
Sexual violence against women often leads to posttraumatic stress disorder (PTSD), a mental illness characterized by intrusive thoughts and memories about the traumatic event (1). These experiences may increase ruminations, which are the repeated rehearsal of thoughts, typically negative and about the self. These mental processes are obviously generated by the brain but often felt in the body. MAP Training My BrainTM is a novel clinical intervention that combines mental training of the brain with physical training of the body (2,3). Each training session begins with 20-min of sitting meditation, followed by 10-min of slow-walking meditation, and ending with 30-min of aerobic exercise at 60-80% of the maximum heart rate (see MAPTRAINMYBRAIN.com). In previous studies, the combination of mental and physical (MAP) training together significantly reduced symptoms of depression and ruminative thoughts, while reducing anxiety (2,4,5). We also documented positive changes in brain activity during cognitive control and whole-body oxygen consumption in various populations. In the present pilot study, we asked whether the combination of meditation and aerobic exercise during MAP Training would reduce trauma-related thoughts, ruminations and memories in women and if so, whether the combination would be more effective than either activity alone. To test this hypothesis, MAP Training was provided to a large group of women (n = 105), many of whom had a history of sexual violence (n = 32). Groups were trained with 1) MAP Training, 2) meditation alone, 3) aerobic exercise alone or 4) not trained. Individuals in training groups completed two sessions a week for at least 6 weeks. MAP Training My BrainTM significantly reduced posttraumatic cognitions and ruminative thoughts in women with a history of sexual violence, whereas meditation alone and exercise alone did not. MAP Training significantly enhanced a measure of self-worth, whereas meditation and exercise alone did not. Similar positive effects were observed for all participants, although meditation alone was also effective in reducing trauma-related thoughts. Overall, these data indicate the combination of meditation and exercise is synergistic. As a consequence, MAP Training is preferable and especially so for women who have experienced sexual violence in their past. Simply put,